Knowledge Representation and Management: Towards Interoperable Medical Terminologies - Rassinoux, A.-M.; Section Editor for the IMIA Yearbook Section on Knowledge Representation and Management (Yearbook of Medical Informatics, 2009)
Objective To summarize current outstanding research in the field of knowledge representation and management.Methods Synopsis of the articles selected for the IMIA Yearbook 2009.Results Four excellent papers have been selected for the section knowledge representation and management. All these papers are concerned with terminological systems whether it is to detect equivalent concept definitions, to structure narratives, to compare existing lay and professional terms or to reformulate the SNOMED’s logical formalism towards a more expressive language.Conclusion The ability of one computer system to access and use the resources of another system becomes crucial in a world where the amount of electronically stored data increases continuously. The selected papers for the section knowledge representation and management corroborate that interoperable medical terminologies play a growing and strategic role in Electronic Health Record (EHR) systems. Indeed, they allow data in clinical systems to be defined in a more uniform and granular manner, thus leading to flexible, semantically interoperable and trust-worthy health information systems.
Keywords: Description logic; concept definitions; structured narrative; interoperable terminology